CYP19 Genetic Polymorphism Haplotype AASA Is Associated with a Poor Prognosis in Premenopausal Women with Lymph Node-Negative, Hormone Receptor-Positive Breast Cancer. (14th November 2013) - Kuo, Sung-Hsin; Yang, Shi-Yi; Lien, Huang-Chun; Lo, Chiao; Lin, Ching-Hung; Lu, Yen-Sen; Cheng, Ann-Lii; Chang, King-Jeng; Huang, Chiun-Sheng
Abstract : Given the critical role of CYP19 in estrogen synthesis, we investigated the influence of CYP19 gene polymorphisms on the clinical outcome of lymph node- (LN-) negative, hormone receptor- (HR-) positive early breast cancers. Genotyping for the CYP19 polymorphisms rs4646 (A/C), rs1065779 (A/C), CYP19 (TTTA)n (short allele/long (S/L) allele using the 7 TTTA repeat polymorphism as the cut-off), and rs1870050 (A/C) was performed on 296 patients with LN-negative, HR-positive breast cancers. All patients received adjuvant hormonal therapy. Associations were examined between these 4 genotypes and 6 common haplotypes of CYP19 and distant disease-free survival (DDFS), disease-free survival (DFS), and overall survival (OS). Patients were divided into the 6 subhaplotypes of CCLA (41.1%), AASA (17.1%), CASA (11.9%), CCLC (8.9%), CCSA (7.5%), AASC (8.9%), and others (4.6%). In premenopausal patients, haplotype AASA was significantly associated with a poor DDFS (adjusted hazard ratio (aHR), 3.3; P = 0.001 ), DFS (aHR, 2.5; P = 0.0008 ), and OS (aHR, 2.9; P = 0.0004 ) after adjusting for age, tumor size, tumor grade, estrogen receptor status, progesterone receptor status, chemotherapy, pathology, adjuvant hormone therapy, menopausal status, and radiotherapy. Furthermore, haplotype AASA remained a negative prognostic factor for premenopausal patients receiving adjuvant chemotherapy in terms of DDFS (aHR, 4.5; P = 0.0005 ), DFS (HR, 3.2; P = 0.003 ), and OS (HR, 6.4; P = 0.0009 ). However, in postmenopausal patients, haplotype AASA was not associated with a poor prognosis, whereas the AASC haplotype was significantly associated with a poor DFS (aHR, 3.1; P = 0.03 ) and OS (aHR, 4.4; P = 0.01 ). Our results indicate that, in patients with LN-negative, HR-positive breast cancers, genetic polymorphism haplotype AASA is associated with poor survival of premenopausal women but does not affect survival of postmenopausal women.